HEAVY METALS SPATIAL VARIABILITY AMONG DUMPSITES IN KANO METROPOLIS, KANO STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2020)
The study reported the spatial distribution of some selected heavy metals (Zn, Pb. Cd. Cr and Ni) among dumpsites in Kano Metropolis, Kano State, Nigeria. Forty-two soil samples (from seven municipal solid waste dump sites) were analysed using Flame atomic absorption spectrophotometer.  The mean concentration of heavy metals in the surface soils (0-15 cm) indicated that Zn (0.10 mg/ kg), Pb (1.03, mg/kg), Cd (0.007 mg/kg), Cr (0.15 mg/kg) and Ni (0.17 mg/kg) while the mean value of heavy metals in the sub surface soils (15-30) were Zn (0. 11 mg/ kg), Pb (0.26mg/kg), Cd (0.008 mg/kg), Cr (0.15 mg/kg) and Ni (0.17 mg/kg). The mean concentrations of the five studied heavy metals (Zn, Pb, Cd, Cr and Ni) were below WHO (2007) and DPR (2002) standard. Results of heavy metal spatial variability showed that concentration of Zn and Pb in soils were significantly different (P  0.05) among the dumpsites. Pearsonâ€™s correlation coefficient showed moderate positive and significant associations between Zn and Cd (r = 0.580, P
Keywords: FAAS, Concentration, Municipal Solid waste, Person’s coefficient, NESREA